2005
DOI: 10.1177/000331970505600510
|View full text |Cite
|
Sign up to set email alerts
|

Starting with Rosuvastatin in Primary Hyperlipidemia—

Abstract: The authors investigated the effects of rosuvastatin, beyond its lipid-lowering activity, on several nonlipid metabolic variables, along with its safety and tolerability, in patients treated for primary hyperlipidemia. Patients (n = 55) with primary hyperlipidemia were open-label assigned to the recommended starting dose of rosuvastatin 10 mg/day, and serum metabolic variables were measured at baseline and after 8 and 20 weeks. Treatment with rosuvastatin produced significant reductions in total cholesterol, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
2
7
0
2
Order By: Relevance
“…With respect to their impact on IS, previous reports of rosuvastatin showed no effect (15)(16)(17) or even worsening of IR (18). Atorvastatin was neutral in our study which is consistent with most previous reports (8,19), although some demonstrated amelioration (20) or worsening of IR (21).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to their impact on IS, previous reports of rosuvastatin showed no effect (15)(16)(17) or even worsening of IR (18). Atorvastatin was neutral in our study which is consistent with most previous reports (8,19), although some demonstrated amelioration (20) or worsening of IR (21).…”
Section: Discussionsupporting
confidence: 91%
“…The RSV was selected due to its anticipated significant absolute LDL cholesterol reduction and the favorable safety profile with the starting dose of 10 mg/d. 12 The addition of ezetimibe to the statin was decided because it is well documented that this combination reduces LDL cholesterol by the equivalent of around 3 doublings of the statin dose. 13 All patients were preoperatively screened in accordance with the recommendations proposed by the American Heart Association/American College of Cardiology Task Force.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…However, no influence on renal function parameters (creatinine, eGFR) has been shown in patients with primary hyperlipidemia receiving rosuvastatin 10 to 20 mg/day for 12 to 20 weeks of therapy. 44,45,115,116 Rosuvastatin and renoprotection: a mechanistic approach. Potential mechanisms that could explain the "renoprotective" actions of rosuvastatin include immunomodulatory properties, regulation of endothelial function, tissue protective and antioxidant properties, as well as beneficial effects on renal hemodynamics.…”
Section: Renoprotective Effectsmentioning
confidence: 99%